THE INTEGRATED ISLAMIC SCHOOL’S CHARACTERISTICS AND STRATEGIES FOR HUMAN RESOURCE SUPERVISION - Fantika Febry Puspitasari; Ahmad Sulaiman; Supriyanto Supriyanto (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
The Integrated Islamic School (Sekolah Islam Terpadu) is known for its rapid development trend in the last decade. The development of the integrated Islamic School runs with the growth of interest to a pure Islamic Education. Appearing as an Islamic institution integrating both religious and secular knowledge, the Integrated Islamic School is able to master the market among the Muslim population. This article aims to scrutinize the characteristics and strategies of the school to expand amid the competitive Indonesian education market through human resource supervision. This research uses a qualitative approach. Data collection techniques were observation, interviews, and documentation. The results showed that the characteristics and strategies of the integrated Islamic School-based human resource supervision encompass political stability, strong Islamic symbols, Islamic personal development programs, inclusive scholarships, and incorporating Islamic populism. These characteristics and strategies attribute the integrated Islamic school as modern, advanced yet religious. In addition, the schools are exclusive in recruiting teachers, pragmatic in using Islamic symbols, and idealistic in the curriculum. Interestingly, this research evokes the integrated Islamic school’s two faces. Internally, it affiliates with an exclusive organization and ideology (Muslim Brotherhood), but simultaneously the school publicly shows inclusive nuances to the society.